Advanced train tracking system using Wi-Fi - Mustafi, Arpita; Khan, Reezwanur Rahman; Ahmed, Mahi Uddin; Biswas, Stafy Shalomy (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.